The protective effect of kaempferol on heart via the regulation of Nrf2, NF‐κβ, and PI3K/Akt/GSK‐3β signaling pathways in isoproterenol‐induced heart failure in diabetic rats. Issue 3 (12th March 2019) - Zhang, Long; Guo, Zhaoxia; Wang, Yan; Geng, Jun; Han, Shuyi
Abstract: This study was designed to delineate the effect of kaempferol (KF) on heart failure (HF) in diabetic rats. Streptozotocin‐induced male diabetic rats received KF orally at 10 and 20 mg/kg for 42 consecutive days. In last 2 days of the experimental period, isoproterenol was subcutaneously injected at 85 mg/kg to induce HF. The hearts were processed for hemodynamic, biochemical, molecular, and histological investigations. Systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure were elevated in KF‐treated HF‐induced diabetic rats. Moreover, KF treatment resulted in decreased fasting blood glucose and glycosylated hemoglobin levels with increased serum insulin levels. Besides, serum cardiac injury markers like troponin‐I, creatine kinase‐muscle/brain, lactate dehydrogenase, and brain natriuretic peptide levels were significantly reduced in KF treatment. KF treatment has shown decrease in cardiac heme oxygenase‐1, nuclear factor erythroid 2–related factor 2 (Nrf‐2), and γ‐glutamylcysteine synthetase with increased Keap1 mRNA levels. The cardioprotection of KF was improved by inhibition of apoptosis via blocking phosphorylation of Akt/glycogen synthase kinase (GSK)‐3β and p38 mitogen‐activated protein‐kinase/extracellular signal‐regulated kinases signaling pathways in HF‐induced diabetic rats. Moreover, reduced cardiac apoptosis in KF treatment was confirmed by decreased terminal deoxynucleotidyl transferase dUTP nick‐end labeling (TUNEL) positive cells, histopathological changes in HF‐induced diabetic rats. Therefore, the cardioprotective effect of KF is attributed to the regulation of Nrf2, nuclear factor kappa‐light‐chain‐enhancer of activated B cells, and Akt/GSK‐3β signaling pathways in HF‐induced diabetic rats.